An Evaluation Of The Level Of Dental Awareness Among The School-Age Population In Central India - Gaikwad , Rahul N (International Journal of Psychosocial Rehabilitation, 2020)
Background: It has been reported by professionals in the field of dentistry that the general population pays very little attention to their oral health, despite the fact that having healthy teeth and gums is one of the most important aspects of overall health. If you start taking care of your gums and teeth from a young age, you’ll have healthier gums and teeth as you get older. The purpose of this study was to investigate the levels of oral hygiene knowledge and practise held by school-aged children in central India who were between the ages of 10 and 15 years old. Material and methods: A cross-sectional study was conducted on 879 kids between the ages of 10 and 15; 500 of them (or 56.88 percent) were boys, while 379 (or 43.12 percent) were girls. A self-administered, structured questionnaire in English was used to conduct the survey, which consisted of 20 multiple-choice questions about the manner and method of brushing and flossing teeth, the necessity of rinsing the mouth afterward, the use of dental floss, the frequency of dental visits, the prevention and treatment of tooth decay, and the impact of fluoride on teeth. Student’s t-test was used to analyse the differences in mean scores by age and gender, and the chi-squared test was used as a test of significance for the proportions. Descriptive statistics using frequency distribution, mean percentage scores, and standard deviation were also calculated. Results: The mean percentage knowledge scores were 4.11+ 1.46 and for practice scores were 4.50 +1.365 for all the children. Among the total number of participants(879) , 98.1% of them use tooth brush to clean their teeth and dental floss was found to be used by 35.3% of the participants. The participants of this study show high awareness (66.1%) of the link between oral health and systemic well-being, while only 33.9% of the participants were unaware of this fact. Conclusion: These results indicate a positive but a low level of oral health awareness among 10–15-year-old school children in Central India. The present study showed the need for the oral health education of the school children aiming at improving oral health knowledge and continuous implementation of school oral health promotion programs.